Incidence and Severity of Acute Myocardial Injury after Thoracic Surgery: Effects of Nicorandil - K. V. Protasov; O. A. Barahtenko; E. V. Batunova; E. A. Rasputina (Рациональная фармакотерапия в кардиологии)
Aim. To study the perioperative dynamics of myocardial injury biomarkers high-sensitivity cardiac troponin I (hs-cTnI), ischemia-modified albumin (IMA) and soluble ST2 (sST2) when taking nicorandil in lung cancer patients with concomitant coronary heart disease (CHD) undergoing surgical lung resection.Material and methods. The study included 54 patients (11 women and 43 men) with non-small cell lung cancer and concomitant stable CHD who underwent lung resection in the volume of lobectomy or pneumonectomy. Patients were randomly assigned to the nicorandil group (oral administration 10 mg BID for 7 days before and 3 days after surgery; n=27) and the control group (n=27). In the study groups, the perioperative dynamics of hscTnI, IMA and sST2, determined in the blood before and 24 and 48h after surgery, were compared. We calculated the incidence of acute myocardial injury in the groups, which was diagnosed in cases of postoperative hs-cTnI increase of more than one 99th percentile of the upper reference limit. The associations of nicorandil intake and acute myocardial injury were evaluated.Results. The groups were comparable in gender, age, basic clinical characteristics, as well as baseline levels of myocardial injury biomarkers. After the intervention, both samples showed an increase in the hs-cTnI and sST2 levels and a decrease in IMA concentration (all p<0.02 for related group differences). In the nicorandil group, in comparison with the control one, 48h after surgery, we found lower mean levels of hs-cTnI [16.7 (11.9;39.7) vs 44.3 (15.0;130.7) ng/l; p<0.05) and sST2 [62.8 (43.6;70.1) vs 76.5 (50.2;87.1) ng/ml; p<0.05), concentration increase rates of hs-cTnI [14.8 (0.7;42.2) vs 32.5 (14.0;125.0) ng/l; p<0.01) and sST2 [24.4 (10.3;42.4) vs 47.4 (17.5;65.3) ng/ml; p<0.05), as well as highest concentrations for the entire postoperative period of hs-cTnI [30.7 (12.0;53.7) vs 79.0 (20.3;203.3) ng/L, p<0.01] and sST2 [99.8 (73.6;162.5) vs 147.8 (87.8;207.7) ng/mL; p<0.05]. The serum IMA decreased when taking nicorandil to a greater extent [-8.0 (-12.6; -2.0) vs -2.7 (-6.0; +5.5) ng/ ml; p<0.01] 24h after surgery. Acute myocardial injury was diagnosed in 7 people in the nicorandil group (25.9%) and in 15 in the control one (55.6%; pχ2=0.027). The adjusted odds ratio of acute myocardial injury when taking nicorandil was 0.35 (95% confidence interval 0.15-0.83, p=0.017).Conclusion. Taking  nicorandil  in patients with lung cancer and concomitant CHD  who underwent  surgical  lung resection is associated  with a lower postoperative  increase in hs-cTnI  and sST2  and a reduced risk of acute myocardial  injury, which may indicate the cardioprotective effect of nicorandil under acute surgical stress conditions.